PENGARUH WORK MOTIVATION, JOB RESOURCES, DAN WORK ENGAGEMENT TERHADAP PERILAKU PROAKTIF - , Lintang Ayuninggar, SE., Dr. Amin Wibowo, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
An important issue in todayâs human resource management is to have employees who can perform with proactive behavior. Unlike the business environment that prevailed a decade ago, the recent economic downturn in developed countries and the competition force company employees to perform not only better but also quicker in response to market demand. Hence, having employees who actively seek more responsibility is desired. This study is based on earlier research and critically examines the antecedents of proactive behavior. We include three forms of work motivation (job self efficacy, role breadth self efficacy, and role orientation), job resources, and work engagement in the model to figure out their effects on proactive behavior. Adding absorption as another dimension of work engagement, this study examined the relationship between job self efficacy, role breadth self efficacy, role orientation job resources, work engagement, and proactive behavior using structural equation modeling.